Semi-clathrate hydrate process of methane in porous media-mesoporous materials of SBA-15. (15th May 2018) - Zhao, Jianzhong; Zhao, Yangsheng; Liang, Weiguo; Song, Su; Gao, Qiang
Highlights: The pressure and temperature of hydrate formation in mesoporous materials of SBA‑15. The kinetics of hydrate formation at various initial pressure and promoters. The effect of THF and TBAB on the hydrate formation in mesoporous materials. Abstract: The hydrate based technology process in porous media is an effective method for gas storage and separation. The formation of methane hydrate in SBA-15, an ordered mesoporous silicon material, was measured with tetrahydrofuran (THF) and tetra-n-butyl ammonium bromide (TBAB) aqueous solution at different pressure and temperature·THF and TBAB were selected to lower the equilibrium pressure at which the gas hydrates can efficiently formed. At the experimental condition of 1.8 MPa–2.0 MPa, SBA-15 was proved to be effective to methane uptake in the hydrates. The results showed that mesoporous silica can help to get the fast-kinetic formation of methane hydrates. The temperature was almost steady and only had two slight increase no more than 0.5 K. The pressure dropped rapidly and then became gentle, which translated into an increase in gas uptake rapidly in the beginning of 100 min and then maintained stable till the end. The reaction rate quickly reached the peak then rapidly dropped and slowly decayed. The desirable kinetics parameters of final gas uptake capacity, average of reaction rate and conversion of gas to hydrate (%) were obtained at higher pressure and lower temperature while THF was better than TBAB. A gas uptake capacity of 91.13 mmol methane gas per mole water was achieved when the hydrates were formed in the presence of THF with SBA-15.